2013
DOI: 10.1007/978-1-62703-345-9_3
|View full text |Cite
|
Sign up to set email alerts
|

Using Yeast to Study Potassium Channel Function and Interactions with Small Molecules

Abstract: Analysis of ion channel mutants is a widely used approach for dissecting ion channel function and for characterizing the mechanisms of action of channel-directed modulators. Expression of functional potassium channels in potassium-uptake-deficient yeast together with genetic selection approaches offers an unbiased, high-throughput, activity-based readout that can rapidly identify large numbers of active ion channel mutants. Because of the assumption-free nature of the method, detailed biophysical analysis of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“… 32 34 Previous studies demonstrated that different Kir3 family members were incapable of rescuing SGY1528 trk1 Δ trk2 Δ growth but that incorporation of Kir3 activating mutations could rescue the yeast under low potassium conditions. 19 , 20 Hence, we reasoned that it should be possible to devise a selection scheme to identify exogenous Kir3 activators by looking for a gain-of-function (GOF) effect under low potassium conditions similar to the strategy used to identify activating mutations of Kir3 19 , 20 and other potassium channels 14 , 16 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… 32 34 Previous studies demonstrated that different Kir3 family members were incapable of rescuing SGY1528 trk1 Δ trk2 Δ growth but that incorporation of Kir3 activating mutations could rescue the yeast under low potassium conditions. 19 , 20 Hence, we reasoned that it should be possible to devise a selection scheme to identify exogenous Kir3 activators by looking for a gain-of-function (GOF) effect under low potassium conditions similar to the strategy used to identify activating mutations of Kir3 19 , 20 and other potassium channels 14 , 16 …”
Section: Resultsmentioning
confidence: 99%
“… 6 A number of recent advances have aided in the prosecution of high-throughput small molecule screens against potassium channel targets, including development of a fluorescent dye that can detect thallium, an ion that permeates many potassium channels, 60 63 and the use of a yeast-based potassium transport strain. 16 , 22 , 64 , 65 Nevertheless, there remains a need to expand the range of systems that can be used to develop new ion channel modulators.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One aim of this study was to compare the results of yeast complementation assays with data from PLB measurements. Yeast complementation assays compare the growth of potassium uptake deficient (trk1/trk2) yeasts expressing heterologous ion channels versus growth of trk1/trk2yeasts without expression of heterologous ion channels on media with a low potassium concentration (Bagriantsev & Minor, 2013). Fig.…”
Section: Discussionmentioning
confidence: 99%